BİR HİKÂYE MECMUASINDA YER ALAN İBN SÎNÂ HİKÂYESİ ÜZERİNE DEĞERLENDİRME. - FİDAN, Gülşah Gaye (Electronic Turkish Studies)
great personalities that leave deep traces in the society, they have a legendary life besides their historical life. They have become specimens of the people sown ideal life, thought sand purposes in the eyes of the people. Their adventures, their loves, their lives are not the truth but the ideal created by the people in their imagination. İbn Sînâ was also idealized in the eyes of the Turkish people as one of the great scientists raised by the Islamic civilization. Born in the village of Efşene near Buhara approximately in 980- 981, Ibn Sînâ died in Hemedan in 1037. Ibn Sînâ has collected all the sciences, especially mathematics, philosophy, astronomy, medicine, Islamic law, music, and has written many works on these subjects andearned a great reputation in the Islamic World while still alive. The great reputation that has survived for centuries, both in life and after death, has become legendary among the people, became a hero of extraordinary adventures, and many stories about mythical life have come to the body. In these cond half of the XVI. century, Dervish Hasan Medhi's Esrâr-ı Hikmet, in the XVII. Century, Seyyid Ziyaeddin Yahya's work called "Gencine-i Hikmet", was wrote up as works that took the stories of Ibn Sînâ. Apart from these works, there are also copies of Ibn Sînâ story whichs editor unspecified. In this study, firstly, the works on the books and novels about İbn Sînâ are mentioned and the story of "Kitâb-ı Ebû Ali Sinân", which is included in a book published in the Istanbul Municipal Library Atatürk library by the registration number as K_0633, is presented. Similarities and differences of this new version with other versions have been revealed.